Student and Faculty Perceptions of the Quality of Online Learning Experiences - Ward, Michael E.; Peters, Gary; Shelley, Kyna (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
Some faculty members are reluctant to offer online courses because of significant concerns relative to the impact of such formats on the quality of instruction, learning, and participant interaction. Faculty members from The University of Southern Mississippi implemented synchronous interactive online instruction (SIOI) in the spring of 2007. This article explores the rationale for use of the particular technology, faculty conclusions regarding implementation of the technology, and the impact of the technology on instruction and learning. Comparisons by students of the quality of the learning experience in this environment with the quality of learning in face-to-face and asynchronous online learning environments were also analyzed. The study finds that instructors and students view SIOI favourably. The mean student ratings for the dimensions of instructional quality were the same for SIOI and face-to-face course formats in all but one dimension, but mean ratings for SIOI and face-to-face formats were consistently higher than those for asynchronous online instruction. The single exception was for the dimension, ease of access to the course; the SIOI and asynchronous online formats were rated higher than the face-to-face format in this quality dimension. These findings suggest that it is possible to achieve levels of effectiveness in an online instructional format similar to those that are realized in face-to-face delivery. However, there is slight, though not statistically significant, evidence of concern about the quality of student collaboration in SIOI-enabled courses. Thus, instructors will need to capitalize on available mechanisms for interaction and collaboration.